Protective Effects of the Complement Inhibitor Compstatin CP40 in Hemorrhagic Shock - van Griensven, Martijn; Ricklin, Daniel; Denk, Stephanie; Halbgebauer, Rebecca; Braun, Christian K; Schultze, Anke; Hönes, Felix; Koutsogiannaki, Sofia; Primikyri, Alexandra; Reis, Edimara; Messerer, David; Hafner, Sebastian; et al. (Shock, 2019)
Trauma-induced hemorrhagic shock (HS) plays a decisive role in the development of immune, coagulation, and organ dysfunction often resulting in a poor clinical outcome. Imbalanced complement activation is intricately associated with the molecular danger response and organ damage after HS. Thus, inhibition of the central complement component C3 as turnstile of both inflammation and coagulation is hypothesized as a rational strategy to improve the clinical course after HS.Applying intensive care conditions, anaesthetized, monitored, and protectively ventilated nonhuman primates (NHP; cynomolgus monkeys) received a pressure-controlled severe HS (60 min at mean arterial pressure 30 mmHg) with subsequent volume resuscitation. Thirty minutes after HS, animals were randomly treated with either an analog of the C3 inhibitor compstatin (i.e., Cp40) in saline (n = 4) or with saline alone (n = 4). The observation period lasted 300 min after induction of HS.We observed improved kidney function in compstatin Cp40-treated animals after HS as determined by improved urine output, reduced damage markers and a tendency of less histopathological signs of acute kidney injury. Sham-treated animals revealed classical signs of mucosal edema, especially in the ileum and colon reflected by worsened microscopic intestinal injury scores. In contrast, Cp40-treated HS animals exhibited only minor signs of organ edema and significantly less intestinal damage. Furthermore, early systemic inflammation and coagulation dysfunction were both ameliorated by Cp40.The data suggest that therapeutic inhibition of C3 is capable to significantly improve immune, coagulation, and organ function and to preserve organ-barrier integrity early after traumatic HS. C3-targeted complement inhibition may therefore reflect a promising therapeutic strategy in fighting fatal consequences of HS.
Keywords: Animals; Male; Complement Inactivating Agents/pharmacology; Macaca fascicularis; Peptides, Cyclic/pharmacology; Shock, Hemorrhagic/blood